A LIFE STUDY OF THE LEAF MINER Liriomyza sativae (DIPTERA: AGROMYZIDAE): A LIFE STUDY OF THE LEAF MINER Liriomyza sativae (DIPTERA: AGROMYZIDAE) (Iraqi Journal of Market Research and Consumer Protection, 2024)
The leaf miner Liriomyza sativae (Diptera: Agromyzidae) is a dangerous pest, causes damage to many plants in Iraq, and in results some economic losses. More than 370 species make up the genus Liriomyza is most common in all of the world's cucumber-cultivation areas. L. sativae is a very harmful pest that affects melons, tomatoes, cucumbers, beans, peas, and pumpkins. The majority of parasitoid insects that feed on leaves belong to the order Hymenoptera, which is comprised of species that fall under the taxonomic categories of the two families Ichneumonidae and Chalcidoidea.